2010
DOI: 10.1136/thx.2010.150987.43
|View full text |Cite
|
Sign up to set email alerts
|

P142 Inflammatory cells in the quadriceps of COPD patients and response to resistance training

Abstract: infrequently performed in the United Kingdom. We however, have persisted with video assisted thoracoscopic (VATS) LVRS and report the results of our first 200 operations. Patients/methods Surgical candidates for LVRS were selected by a multidisciplinary team approach using radionuclide scintigraphy in all cases. After the initial 20 open cases we adopted policy of two stage bilateral VATS LVRS with the timing of the second operation determined by the patient. 160 patients have completed one-stage LVRS: median … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…These results are in line with observations from Gosker et al who found normal amounts of macrophages in the skeletal muscle of COPD patients. Nevertheless, in other studies, higher immune cell infiltration of the skeletal muscle has been documented in COPD . These conflicting results could be the result of different stages of COPD studied or that we did not specifically select patients with the muscle depleted phenotype for the present trial.…”
Section: Discussionmentioning
confidence: 87%
“…These results are in line with observations from Gosker et al who found normal amounts of macrophages in the skeletal muscle of COPD patients. Nevertheless, in other studies, higher immune cell infiltration of the skeletal muscle has been documented in COPD . These conflicting results could be the result of different stages of COPD studied or that we did not specifically select patients with the muscle depleted phenotype for the present trial.…”
Section: Discussionmentioning
confidence: 87%